2022
DOI: 10.4143/crt.2020.1198
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Efficacy Data and Predictive Clinical Parameters for Treatment Outcomes in Advanced Esophageal Squamous Cell Carcinoma Treated with Immune Checkpoint Inhibitors

Abstract: This study aimed to evaluate the real-world efficacy of immune checkpoint inhibitors (ICIs), and to identify clinicolaboratory factors to predict treatment outcomes in patients with advanced esophageal squamous cell carcinoma (ESCC) receiving ICIs. Materials and MethodsSixty patients with metastatic or unresectable ESCC treated with nivolumab (n=48) or pembrolizumab (n=12) as ≥ second-line treatment between 2016 and 2019 at Asan Medical Center were included. ResultsThe median age of the patients was 68 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
(56 reference statements)
0
28
0
Order By: Relevance
“…Five observational studies reported that PNI was an independent indicator for a shortened OS in cancer patients with immunotherapy (18,19,(26)(27)(28), while PNI was not considered as a prognostic factor for OS in seven studies (20,(29)(30)(31)(32)(33)(34). Pooled analysis of all selected publications revealed that the PNI values higher than the cutoff value predicted a poor OS (pHR = 2.24, 95% CI = 1.57-3.20, Figure 2) in advanced cancer patients treated with immune checkpoint inhibitors.…”
Section: Correlation Between Pretreatment Prognostic Nutritional Inde...mentioning
confidence: 99%
See 1 more Smart Citation
“…Five observational studies reported that PNI was an independent indicator for a shortened OS in cancer patients with immunotherapy (18,19,(26)(27)(28), while PNI was not considered as a prognostic factor for OS in seven studies (20,(29)(30)(31)(32)(33)(34). Pooled analysis of all selected publications revealed that the PNI values higher than the cutoff value predicted a poor OS (pHR = 2.24, 95% CI = 1.57-3.20, Figure 2) in advanced cancer patients treated with immune checkpoint inhibitors.…”
Section: Correlation Between Pretreatment Prognostic Nutritional Inde...mentioning
confidence: 99%
“…Peng et al revealed that a higher level of PNI was associated with better survival outcomes in advanced non-small cell lung cancer (NSCLC) treated with ICIs (18). Kim et al identified that PNI greater than the cutoff was correlated with favorable progressivefree survival (PFS) and overall survival (OS) in advanced esophageal squamous cell cancer (ESCC) with immunotherapy (19). A study by Zaitsu et al showed that PNI was not a significant prognostic factor of immunotherapy in patients with lung cancer (20).…”
Section: Introductionmentioning
confidence: 99%
“…Some key differences between our present study and previous studies on NLR in ESCC under immunotherapy should be highlighted. [18][19][20][21] First, our study reported the most comprehensive clinical outcomes, exhibiting significant differences in ORR, PFS and OS, while two of the four previous studies failed to exhibit the association between NLR (or derived NLR) with PFS, and one study did not analyze the results of OS and responses. Second, the cutoff values of NLR were different.…”
Section: Discussionmentioning
confidence: 77%
“…[14][15][16][17] However, studies on NLR in ESCC are limited. [18][19][20][21] A few studies have attempted to identify the association between NLR and survival in patients with ESCC treated with ICI-containing regimens; however, the findings are inconsistent and they all have common limitations. First, the retrospective nature limited the quality of response evaluation and follow-up, so none of these studies reported the complete panorama of responses and survivals as well as the continuous tracking of NLR at each evaluation; second, patients enrolled in these studies were treated with heterogenous therapeutic strategies, including different single-agent ICIs, dual blockade of PD-1 and CTLA-4, or ICIs combined with surgery, radiotherapy or chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation